Hubungan Antara Obesitas dan Hipertensi dengan Kanker Payudara pada Pasien di Rumah Sakit Siloam Lippo Village Gedung B - Nicoline Naomy Lamria; Heru Sutanto Koerniawan (MEDICINUS, 2024)
Background: Breast cancer has become one of the most common cancers in Indonesia, and being one of the largest contributors to cancer deaths. Several studies have shown association between breast cancer with obesity and hypertension, both as modifiable risk factors. Methods: This study was conducted using unpaired categorical comparativeanalytic method with a case control design. Samples were collected using medical record data using consecutive sampling method. Sample were 160 patients aged 20–55 years at Siloam Lippo Village Hospital Building B; consisting of 80 casegroup samples and 80 control group samples. Data was analysed using Chi-square test. Result: Data analysis resultshowed that there was an association between obesity and breast cancer in patients at Siloam Lippo Village Hospital Building B (p=0.000; OR=11.238; 95% CI=5.360–23.563). There was also association between hypertension and breast cancer in patients at Siloam Lippo Village Hospital Building B (p=0.007; OR=7.567;95% CI=1.648–34.740). Conclusion:There is a significant association between obesity and hypertension with the incident of breast cancer in patients at SiloamLippo Village Hospital Building B.